Experimental study on removal of phenol formaldehyde resin coating from the abrasive disc and preparation of abrasive disc for polishing application - Sabarinathan, P.; Annamalai, V. E.; Vishal, K.; Nitin, M.S.; Natrayan, L.; Veeeman, Dhinakaran; Mammo, Wubishet Degife (Advances in materials science and engineering, 2022)
In the automotive and aerospace industry, abrasive products lodge the major portion of the machining applications. Among that, the coated abrasive disc is used for a finishing application. Once the disc is fully consumed, the disc is unused and considered waste. The present work focuses on removing phenol-formaldehyde resin coating, and the fiber backing is reused for the same coated abrasive disc production application as flexible fiber backing. A sandblasting technique removes phenol-formaldehyde resin coating and embedded abrasive grains. During the fiber backing recovery process, the experimental parameters such as abrasive pressure, abrasive type, abrasive size, and orientation of the disc are varied to find out the optimal surface roughness value for reusing the produced coated abrasive discs. The results highlight that the recovered backing has an abrasive size of 120 mesh pressure of 0.20 MPa, an abrasive type of garnet, and a standoff distance of 1 mm. Surface features such as surface roughness and micrographs of the eroded surface are analyzed. Finally, the recovered backing was reused in the coated abrasive disc production, and the performance of the recovered disc was compared with the standard discs. The recovered fiber backing disc product was similar to a standard fresh disc.